BCG vaccination: a role for vitamin D? - Maeve K Lalor (PLoS ONE, 2011)
BCG vaccination is administered in infancy in most countries with the aim of providing protection against tuberculosis. There is increasing interest in the role of vitamin D in immunity to tuberculosis. This study objective was to determine if there was an association between circulating 25(OH)D concentrations and BCG vaccination status and cytokine responses following BCG vaccination in infants.Blood samples were collected from UK infants who were vaccinated with BCG at 3 (n = 47) and 12 (n = 37) months post BCG vaccination. These two time-points are denoted as time-point 1 and time-point 2. Two blood samples were also collected from age-matched unvaccinated infants (n = 32 and 28 respectively), as a control group. Plasma vitamin D concentrations (25(OH)D) were measured by radio-immunoassay. The cytokine IFNγ was measured in supernatants from diluted whole blood stimulated with M.tuberculosis (M.tb) PPD for 6 days.58% of infants had some level of hypovitaminosis (25(OH)D <30 ng/ml) at time-point 1, and this increased to 97% 9 months later. BCG vaccinated infants were almost 6 times (CI: 1.8-18.6) more likely to have sufficient vitamin D concentrations than unvaccinated infants at time-point 1, and the association remained strong after controlling for season of blood collection, ethnic group and sex. Among vaccinees, there was also a strong inverse association between IFNγ response to M.tb PPD and vitamin D concentration, with infants with higher vitamin D concentrations having lower IFNγ responses.Vitamin D may play an immuno-regulatory role following BCG vaccination. The increased vitamin D concentrations in BCG vaccinated infants could have important implications: vitamin D may play a role in immunity induced by BCG vaccination and may contribute to non-specific effects observed following BCG vaccination.